Prion protein fragment (106–126) activates NLRP3 inflammasome and promotes platelet-monocyte/neutrophil interactions, potentially contributing to an inflammatory state - Rashmi Verma; Jyotsna Kailashiya; Avijit Mukherjee; Rameshwar Nath Chaurasia; Debabrata Dash (Frontiers in Cell and Developmental Biology)
IntroductionPrion diseases are neurodegenerative disorders where infectious prion proteins (PrP) featuring an amyloidogenic amino acid sequence, PrP (106–126), accumulate in the brain leading to neuroinflammation while it can also access circulation by breaching the blood-brain barrier. Platelets are highly sensitive cells in blood, which have been widely employed as “peripheral” model for neurons. In addition to their stellar roles in hemostasis and thrombosis, platelets are also known to function as immune cells and possess necessary components of functional inflammasome. This study demonstrates that prion proteins drive inflammasome assembly in platelets and upregulate activity of caspase-1, a critical readout of functional inflammasomes.MethodsFlow cytometric analysis was performed to measure intracellular ROS levels, caspase-1 activity, and platelet-monocyte/neutrophil interactions. Microscopy was used to assess the co-localization of NLRP3 and ASC.ResultsInflammasome activation is fuelled by reactive oxygen species (ROS) generated in prion-stimulated platelets that eventually leads to formation of platelet-monocyte/neutrophil aggregates, which was prohibited by small-molecule inhibitors of either caspase-1 or ROS.DiscussionThus, in addition to their neurotoxic effects on neuronal cells and stimulation of pro-coagulant activity in platelets, prions also unleash an inflammatory response in the organism.